2013
DOI: 10.4314/sokjvs.v11i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical facilities and processing operations of major abattoirs in North-western states of Nigeria

Abstract: The study was carried out to evaluate the physical facilities of four major abattoirs in Northwestern states of Nigeria these are: Mayanka abattoir in Kano, Kara abattoir in Sokoto, Zango abattoir Zaria and Kawo abattoir in Kaduna. The facilities of these abattoirs were evaluated based on their presence and functional status. Pictures were taken using digital camera to document conditions of the infrastructure and activities of the butchers. The present study showed that the basic components were in a deplorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 3 publications
6
37
1
Order By: Relevance
“…Majority of the slaughterhouses lack lairage facilities, whenever it is present it is either under-utilized or not put into use, and most of the time it is in a deplorable state with very poor level of hygiene. Majority of the lairages in slaughterhouses in Oyo State are not routinely cleaned, this further supports the findings of previous studies, that most slaughterhouses in Nigeria do not have functional lairages (Lawan et al, 2013). Also, the usage of lairage if present at all for resting of livestock before slaughtering is poor, which is in line with the assertion of Adeyemo et al (2009), that lairage has been largely implicated as a point for cross contamination among animals being rested after transportation from long distance.…”
Section: Discussionsupporting
confidence: 78%
“…Majority of the slaughterhouses lack lairage facilities, whenever it is present it is either under-utilized or not put into use, and most of the time it is in a deplorable state with very poor level of hygiene. Majority of the lairages in slaughterhouses in Oyo State are not routinely cleaned, this further supports the findings of previous studies, that most slaughterhouses in Nigeria do not have functional lairages (Lawan et al, 2013). Also, the usage of lairage if present at all for resting of livestock before slaughtering is poor, which is in line with the assertion of Adeyemo et al (2009), that lairage has been largely implicated as a point for cross contamination among animals being rested after transportation from long distance.…”
Section: Discussionsupporting
confidence: 78%
“…The practice of scavenging for water observed in Oyo state abattoir (Figure 2 & 8) is of significant public health implication as it increases the potentials of water borne disease agents being transferred to meat products. This finding is similar to that of Lawan et al, (2013) who observed that in four abattoirs surveyed in northern Nigeria, there was no regular supply of portable water and electricity. Water was usually obtained from truck pushers, who sold water from unidentified sources for carcass washing.…”
Section: Discussionsupporting
confidence: 80%
“…Occasionally the butchers sourced water from nearby streams. The meat inspectors in the study of Lawan et al,(2013) adduced this deplorable state to government's insensitivity and lack of concern towards general management of abattoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of construction style, components of an abattoir and other services should include the following; Lairage, slaughter hall, gut and tripe room, detained meat room, offal room, condemned meat room, hide and skin room. Others include cutting room, refrigeration room, supply of hot and cold water under pressure, veterinary inspection room, disinfection facilities, personnel welfare room, veterinary office and facilities for condemned meat offal or carcass disposal; incinerator, chemical treatment and disposal (Lawan et al, 2013). In most developing countries such as Nigeria, there are three main types of abattoirs, namely, the line slaughter, the slaughter slab and the batch systems.…”
Section: Introductionmentioning
confidence: 99%